Process for green synthesis of hydrotalcite through forced molecular recombination diffusion technology
Through forced molecular recombination diffusion technology, the problems of many by-products, difficult industrial wastewater treatment and poor thermal stability in hydrotalcite synthesis process are solved, and the preparation of magnesium-aluminum hydrotalcite with high purity and high thermal stability are achieved, which is suitable for a variety of Application field.
Patent Information
- Application Number
- CN202411338131.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-03
AI Technical Summary
The existing hydrotalcite synthesis process has problems such as many by-products, high cost of industrial wastewater treatment, harsh synthesis conditions, and poor product purity and thermal stability, especially in PVC processing and forming applications.
Using forced molecular recombinant diffusion technology, magnesium-aluminum hydrotalcite with high purity and excellent thermal stability is prepared through low-temperature primary grinding, heating and high-pressure grinding, ultrasonic dispersion and microwave heating, combined with the use of modifiers.
It has achieved clean production without by-products, with a main component content of the product exceeding 97%, and the thermal stability effect is equal to or better than hydrotalcite prepared by hydrothermal sulfate. It is suitable for PVC thermal stabilizers, cable and wire stabilizers and high-transparent agricultural films. Anti-UV absorber.
Smart Images

Figure CN119240767A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrotalcite synthesis, and in particular to a process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology. Background Art
[0002] Magnesium-aluminum hydrotalcite (Mg-Al-LDHs) is a very typical three-dimensional layered anionic compound. Due to its special layered structure and strong anion exchange capacity, Mg-Al-LDHs is widely used in many fields such as thermal stability and flame retardancy of polymers, UV absorbers for pesticide films, flame retardants for cables, industrial catalysis, photoelectrochemistry, drug release, plastic modification and wastewater treatment. At the same time, parameters such as grain size, aspect ratio and specific surface area of Mg-Al-LDHs have a direct impact on its dispersibility, heat aging resistance, colorability and adsorption performance in polymers.
[0003] At present, the main methods for preparing magnesium-aluminum hydrotalcite include co-precipitation, sulfate hydrothermal method, ion exchange method, etc. Although these conventional methods are relatively simple in process, they have various disadvantages such as uneven synthesized hydrotalcite particles, large particle size, the layer structure cannot be completely restored, the product purity is not high, the production process has serious three wastes and high energy consumption.
[0004] Around 2015, China developed a large-scale green synthesis method for hydrotalcite, which was mainly obtained by grinding industrial-grade magnesium hydroxide and aluminum hydroxide at room temperature and then synthesizing them by high-temperature hydrothermal reaction. However, the main problem of this synthesis method is that the main component of the obtained product is only 60-85% (i.e., the purity is low). Therefore, in the application of PVC processing and molding, the thermal stability effect is not as good as the hydrotalcite product synthesized by sulfate hydrothermal method. Therefore, the hydrotalcite product synthesized by this method has great limitations. In this case, the researchers conducted a large number of experiments, such as raw material grinding; replacing part of magnesium hydroxide with magnesium bicarbonate; pressurized reaction; water quality replacement, addition of additives; and other methods, but still failed to achieve the effect of sulfate hydrothermal synthesis. At present, the more commonly used hydrotalcite production technology is the hydrothermal process, which uses soluble metal salts as raw materials. The ion process can better control the morphology of hydrotalcite crystals and prepare hydrotalcite particles with different grain sizes, aspect ratios, and specific surface areas, so that they can be better applied to different types of polymers. However, this process will produce a large number of salts that have no utilization value, and in order to remove the sodium salt or other salts contained in the hydrotalcite, it must be washed several times, which will produce a large amount of wastewater and by-products, resulting in low production efficiency, increased manufacturing costs, and environmental degradation.
[0005] Chinese patent CN114956142B discloses a supercritical synthesis process of nano hydrotalcite with adjustable crystal form, which also adopts the method of adding ethylene glycol to the emulsion, and then after primary grinding and hydrothermal synthesis, it is modified with lactic acid and melamine, and the hydrotalcite product is obtained after drying. The pressure of the preparation process reaches 8.5 MPa, and the mass ratio of the added amount of ethylene glycol to the product hydrotalcite is also close to 1:1. The thermal stability test result of the final product is not compared with the hydrotalcite synthesized by the magnesium sulfate aluminum sulfate hydrothermal method (sulfate hydrothermal method), and more impurity metal ions are introduced into the product. The product contains more unreacted magnesium hydroxide and aluminum hydroxide raw materials, and the product purity is low.
[0006] Chinese patent CN103108907A discloses a process for preparing hydrotalcite using carbon dioxide with a very small sodium content, but the amount of carbon dioxide introduced is small, the carbon dioxide cannot quickly and fully contact with other solid raw materials, and the crystal morphology cannot be effectively regulated during the growth of hydrotalcite, resulting in poor dispersibility, colorability and thermal stability of the obtained product in the polymer.
[0007] Chinese patent CN112811449A discloses a new method for preparing magnesium aluminum hydrotalcite, which comprises adding diethanolamine and sodium phosphate to a raw material emulsion, and after primary grinding and hydrothermal synthesis, modifying with lactic acid and melamine, and obtaining a hydrotalcite product after drying. The temperature of the preparation process reaches 220°C, and the final thermal stability test result is not compared with the hydrotalcite prepared by the hydrothermal method of magnesium sulfate and aluminum sulfate, and the thermal stability effect cannot be reflected.
[0008] Chinese patent CN107902681A discloses a method for preparing calcium aluminum hydrotalcite, which comprises adding calcium hydroxide, aluminum hydroxide and sodium carbonate into a ball mill, controlling the ball-to-material mass ratio at (8-12):1, the ball mill speed at 200-500 r / min, dry grinding for 2-4 hours, and the ratio of small, medium and large grinding balls (with diameters of 5 mm, 8 mm and 10 mm, respectively) at 1-2:2-3:5-7; mixing the solid mixture with water, and subjecting the solid mixture to microwave hydrothermal crystallization at 600-800 W and 70-90° C. for 5-20 min; washing, filtering and drying to obtain calcium aluminum hydrotalcite; this method will produce a large amount of sodium hydroxide by-product that needs to be treated, and the recovery treatment is difficult, and a large amount of waste water will still be produced. Summary of the invention
[0009] The purpose of the present invention is to develop a process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology to solve the above problems faced by the existing hydrotalcite synthesis process. The process is a production process for hydrotalcite crystals without by-products, clean and easy to industrialize.
[0010] To achieve the above object, the present invention is implemented by the following technical solutions:
[0011] The present invention provides a process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology, the process comprising the following steps:
[0012] S1. Preparation of magnesium-aluminum emulsion: In the presence of water, a magnesium source, an aluminum source and a grinding aid are stirred and mixed to obtain a magnesium-aluminum emulsion, and the emulsion is cryogenically ground for standby use;
[0013] S2, crystallization reaction: dilute the low-temperature ground magnesium aluminum emulsion with water and heat it to a first temperature, then grind it at high temperature and disperse it ultrasonically under closed conditions, and introduce CO into the system after heating it to the first temperature. 3 2- and continue to raise the temperature to a second temperature to perform a crystallization reaction to promote the growth of magnesium-aluminum hydrotalcite grains;
[0014] S3, modification: cooling the crystallization reaction system to a third temperature, then adding a modifier to the system for modification, and continuing to cool to a fourth temperature and filtering or centrifuging to obtain hydrous magnesium aluminum hydrotalcite;
[0015] Wherein, the third temperature is lower than the first temperature;
[0016] S4, drying: drying the hydrous magnesium aluminum hydrotalcite to obtain magnesium aluminum hydrotalcite.
[0017] Specifically, due to the problems of many by-products, high cost of industrial wastewater treatment, and harsh synthesis conditions in the conventional hydrothermal synthesis of magnesium-aluminum hydrotalcite, and the problems of insufficient main component content and lower thermal stability than the product obtained by the sulfate hydrothermal method in the conventional green synthesis process of hydrotalcite after grinding at room temperature, it has great limitations in its application in PVC processing and molding, and does not meet the requirements of practical applications; in this regard, the existing improved process (green synthesis method): ① such as raw material grinding; ② partial replacement of magnesium hydroxide with magnesium bicarbonate; ③ pressurized reaction; ④ water quality replacement, addition of additives; the above methods still do not reach the quality of the product synthesized by the sulfate hydrothermal method; for this reason, the present invention provides the above process to solve the problem.
[0018] The process provided by the invention solves the problem of insufficient hydrotalcite content in the synthesized product in the existing green hydrotalcite synthesis method.
[0019] Furthermore, a process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology: the magnesium source in step S1 is magnesium hydroxide, and the aluminum source is aluminum hydroxide; the grinding aid is used to avoid agglomeration of magnesium-aluminum emulsion, and a polyether grinding aid is selected, and specifically Triton X100 can be selected.
[0020] Furthermore, a process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology is provided: the magnesium-aluminum emulsion comprises the following components: 5.0-16.0 wt% of magnesium source, 5.0-16.0 wt% of aluminum source, 0.01-0.03 wt% of grinding aid and the balance of water.
[0021] Furthermore, a green process for synthesizing hydrotalcite by forced molecular recombination diffusion technology is provided: after low temperature grinding, the magnesium aluminum emulsion does not delaminate for at least 48 hours.
[0022] Specifically, the magnesium aluminum emulsion is fully ground for at least 3 hours, and the suspension formed after grinding does not delaminate for at least 48 hours; the Mg / Al ratio can be selected appropriately according to the subsequent characteristic requirements of the hydrotalcite.
[0023] Furthermore, a process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology: in step S2, the temperature is increased by microwave heating, and the first temperature is not less than 100°C, and the second temperature is not more than 200°C.
[0024] Further, a green process for synthesizing hydrotalcite by forced molecular recombination diffusion technology: Step S2 introduces CO by slowly introducing carbon dioxide gas. 3 2- After the addition is completed, continue to keep the reaction warm for 1 to 6 hours.
[0025] Furthermore, a process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology: the third temperature in step S3 is 55 to 85° C.; the modification time is 1 to 3 hours.
[0026] Furthermore, a process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology: the modifier in step S3 is stearic acid or stearate.
[0027] Specifically, the modifier used in the present invention is preferably stearic acid or stearate such as stearic acid, zinc stearate, barium stearate, calcium stearate, etc. According to the stability requirements of the hydrotalcite product, stearic acid and zinc stearate are preferred. In addition, a high-temperature grinding process can also be performed during the modification process to ensure the production of nano-scale hydrotalcite products.
[0028] Preferably, in the modification process of the present invention, stearic acid can be added for modification for 1 hour, and then stearate can be added for modification for 2 hours.
[0029] Furthermore, a process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology: the drying method in step S4 is boiling fluidized bed drying, blast drying, rake drying or vacuum drying.
[0030] Furthermore, a process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology: the grinding equipment is made of zirconia material, in which zirconia beads with a particle size of 50-100 mm account for 1-8%, zirconia beads with a particle size of 10-50 mm account for 8-12%, zirconia beads with a particle size of 5-10 mm account for 5-15%, and zirconia beads with a particle size of 1-5 mm account for 50-70%.
[0031] In the present invention, the high temperature grinding equipment, ultrasonic dispersion equipment and microwave heating equipment are capable of withstanding a high temperature of 200°C and a steam pressure of 2.5MPa, respectively. The inner lining and grinding beads of the high temperature grinding equipment are made of zirconium oxide or agate, and the outer shell is made of 316L material.
[0032] Beneficial effects of the present invention:
[0033] (1) The present invention uses magnesium hydroxide, aluminum hydroxide, carbon dioxide and a trace amount of an additional grinding aid to perform low-temperature primary grinding, high-temperature and high-pressure grinding, high-temperature ultrasonic dispersion and microwave heating, modification, filtration, drying and other processes to force molecular recombination and diffusion, thereby synthesizing magnesium-aluminum hydrotalcite in a green way, and obtaining a high-quality plastic heat stabilizing additive hydrotalcite product, the main component content of which is greater than 97% (magnesium oxide and aluminum oxide impurities are small). The thermal stability effect of the hydrotalcite prepared by this process is equal to or better than that of the product prepared by the sulfate hydrothermal method under the same formulation conditions.
[0034] (2) The process provided by the present invention is simple to operate, and no three wastes are generated during the production process. By adopting the method of fixing carbon dioxide, the byproduct water can be recycled for many times. The system process solves the problems of unstable thermal stability of products, more three wastes, high energy consumption, and the thermal stability of the later products is not as good as the thermal stability of the products obtained by the sulfate hydrothermal method in conventional production. The process of the present invention can maintain the characteristics of uniform particle size distribution of hydrotalcite crystals, no hardening, and no agglomeration, and is convenient to use. It is widely used in PVC heat stabilizers, cable and wire stabilizers, and high-transparency agricultural film anti-ultraviolet absorbers. A small amount of grinding aids are also added in the process of the present invention to assist grinding, reduce the agglomeration phenomenon of the emulsion, and improve the uniformity of particle size distribution of the obtained product.
[0035] (3) The process of the present invention adopts a method of synthesizing magnesium aluminum hydrotalcite by combining a high-temperature crystallization process with grinding and microwave ultrasonic radiation, and utilizes a mechanochemical method and efficient microwave ultrasonic high-temperature dispersion under high-temperature conditions to make the reactants have a higher reaction activity. Under high-temperature conditions, under mechanical grinding and crushing and ultrasonic microwave dispersion, the raw materials are all at the nanometer level, and the reaction is more complete. Magnesium hydroxide, aluminum hydroxide, and carbon dioxide react according to a stoichiometric ratio, and the process includes nucleation, crystal growth, agglomeration, and crystal crushing; direct high-temperature crystallization is converted into magnesium aluminum hydrotalcite, and grinding and ultrasonic microwave dispersion are performed under high-temperature conditions at the same time to make the grain size more uniform and complete, ultimately solving the problems of difficult treatment of magnesium aluminum hydrotalcite by-products, large amount of wastewater treatment in the production process, poor thermal stability of the product, complicated preparation process, large equipment investment, and high production cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0037] Figure 1 This is the infrared spectrum of the magnesium aluminum hydrotalcite obtained in Example 1;
[0038] Figure 2 This is the X-ray diffraction of the magnesium aluminum hydrotalcite obtained in Example 1;
[0039] Figure 3 This is a microscopic morphology of the magnesium aluminum hydrotalcite obtained in Example 1; Figures 4 to 13 The color changes of the samples prepared from the magnesium aluminum hydrotalcite in Example 1 after drying for 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, and 50 min respectively; Figures 14 to 23 The color changes of the samples prepared by the magnesium aluminum hydrotalcite synthesized by the method of CN107902681A after drying for 5min, 10min, 15min, 20min, 25min, 30min, 35min, 40min, 45min, and 50min respectively; Figures 24 to 33 The color changes of the samples prepared from the magnesium aluminum hydrotalcite in Comparative Example 1 after drying for 5min, 10min, 15min, 20min, 25min, 30min, 35min, 40min, 45min, and 50min respectively; Figures 34 to 43The color changes of the samples prepared from the magnesium aluminum hydrotalcite in comparative example 2 after drying for 5min, 10min, 15min, 20min, 25min, 30min, 35min, 40min, 45min, and 50min respectively; Figures 44 to 53 The samples prepared with Concord magnesium aluminum hydrotalcite were dried for 5min, 10min, 15min, 20min, 25min, 30min, 35min, 40min, Color changes after 45min and 50min. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Example 1
[0042] This embodiment 1 provides a process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology, the process comprising the following steps:
[0043] S1, magnesium aluminum emulsion preparation: add 4700g of water into the preparation kettle, start stirring, then add 512g of magnesium hydroxide, 320g of aluminum hydroxide and 1.5g of grinding aid (Triton X100) into the preparation kettle, stir and mix, obtain magnesium aluminum emulsion, grind it fully for at least 3 hours (i.e., low temperature grinding) by grinding equipment at room temperature, and form magnesium aluminum emulsion that does not appear stratification for at least 48 hours after grinding, and set aside;
[0044] S2, crystallization reaction: take the above-mentioned low-temperature ground magnesium aluminum emulsion 3864g and add it to the reactor and add 3500g of water for dilution. After dilution, cover the reactor cover to ensure airtightness, turn on the high-temperature grinding equipment (the grinding equipment is made of zirconium oxide, of which zirconium oxide beads with a particle size of 50-100mm account for 5.0%, zirconium beads with a particle size of 10-50mm account for 10.0%, zirconium beads with a particle size of 5-10mm account for 15.0%, and zirconium beads with a particle size of 1-5mm account for 70%), turn on the ultrasonic dispersion device (100% opening), turn on the microwave heating device (70% opening) and heat it to the first temperature (110°C), and then perform high-temperature grinding and ultrasonic dispersion under closed conditions, and at the same time, after the feed liquid in the reactor is heated to the first temperature, slowly introduce the theoretical amount of carbon dioxide gas (CO 2 ) to introduce CO into the reaction system 3 2- , then continue to slowly heat the mixture to a second temperature (180° C.) by microwave heating, introduce 63.3 g of carbon dioxide through a carbon dioxide metering device, and continue stirring and keeping warm for 6 hours after the introduction is completed to perform a crystallization reaction to promote the growth of magnesium-aluminum hydrotalcite grains;
[0045] S3, modification: after the above-mentioned constant temperature reaction is completed, the reaction system is cooled to the third temperature (80°C), and then 2.0g of zinc stearate is added to the system and kept warm for 1 hour, and then 1.5g of stearic acid is added, and the temperature is raised to 85°C and kept warm for 2 hours; then the temperature is cooled to the fourth temperature (below 80°C), and the material is pumped into a centrifuge by a screw pump for centrifugation, thereby obtaining hydrated magnesium aluminum hydrotalcite;
[0046] S4. Drying: The above-mentioned hydrated magnesium aluminum hydrotalcite is dried by vacuum drying to obtain magnesium aluminum hydrotalcite, wherein the main component content is greater than 97%, the water content in the hydrotalcite is less than 0.5%, the particle size D90 is less than 0.6 μm, and the specific surface area is about 27.0 m 2 / g, and its magnesium-aluminum molar ratio Mg / Al=2.15.
[0047] The hydrotalcite prepared in Example 1 has a similar thermal stability effect to the hydrotalcite prepared by the sulfate hydrothermal method, but the process of this process does not produce three wastes and has low energy consumption. The process provided by the present invention has a high content of the main component of the hydrotalcite in the product, which solves the problem of insufficient hydrotalcite content in the synthetic product of the existing green synthesis method of hydrotalcite.
[0048] The process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology provided in Example 1 uses industrial-grade magnesium hydroxide, aluminum hydroxide, and carbon dioxide to react in a stoichiometric ratio, form nuclei, grow crystals, agglomerate, and crush crystals. Under high temperature conditions, the materials are all at the nanometer level and the reaction is more complete through mechanical grinding and crushing and ultrasonic microwave dispersion. The structure of the target product (hydrotalcite) obtained in Example 1 has been verified by infrared spectroscopy and X-ray diffraction (respectively as shown in FIG. Figure 1 and Figure 2 Its microscopic morphology is as shown in Figure 3 As shown, the particle size distribution is uniform, the specific surface area is large, and the thermal stability is good.
[0049] Example 2
[0050] This embodiment 2 provides a process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology, the process comprising the following steps:
[0051] S1, magnesium aluminum emulsion preparation: add 4700g of water into the preparation kettle, start stirring, then add 395g of magnesium hydroxide, 380g of aluminum hydroxide and 1.0g of grinding aid (Triton X100) into the preparation kettle, stir and mix, obtain magnesium aluminum emulsion, grind it fully for at least 3 hours by grinding equipment at room temperature, and form magnesium aluminum emulsion that does not appear stratification for at least 48 hours after grinding, and set aside;
[0052] S2, crystallization reaction: take the above-mentioned low-temperature ground magnesium aluminum emulsion 3864g and add it to the reactor and add 3200g of water for dilution. After dilution, cover the reactor cover to ensure airtightness, turn on the high-temperature grinding equipment (the grinding equipment is made of zirconium oxide, of which zirconium oxide beads with a particle size of 50-100mm account for 5.0%, zirconium beads with a particle size of 10-50mm account for 10.0%, zirconium beads with a particle size of 5-10mm account for 15.0%, and zirconium beads with a particle size of 1-5mm account for 70%), turn on the ultrasonic dispersion device (100% opening), turn on the microwave heating device (70% opening) and heat it to the first temperature (105°C), and then perform high-temperature grinding and ultrasonic dispersion under closed conditions. At the same time, after the feed liquid in the reactor is heated to the first temperature, start to slowly introduce a theoretical amount of carbon dioxide gas (CO 2 ) to introduce CO into the reaction system 3 2- Then, the temperature was slowly raised to the second temperature (200° C.) by microwave heating, and 63.3 g of carbon dioxide was introduced through a carbon dioxide metering device. After the introduction was completed, stirring and heat preservation were continued for 4 hours to carry out a crystallization reaction;
[0053] S3, modification: after the above isothermal reaction is completed, the reaction system is cooled to a third temperature (85°C), and then 2.0 g of zinc stearate is added to the system and kept warm for 1 hour, and then 1.5 g of stearic acid is added and kept warm for 2 hours; then the temperature is cooled to a fourth temperature (below 80°C), and the material is pumped into a plate and frame filter press by a screw pump for filtration, thereby obtaining hydrous magnesium aluminum hydrotalcite;
[0054] S4. Drying: The above-mentioned hydrated magnesium aluminum hydrotalcite is dried by vacuum drying to obtain magnesium aluminum hydrotalcite, wherein the main component content is greater than 97%, the water content in the hydrotalcite is less than 0.5%, the particle size D90 is less than 1.2 μm, and the specific surface area is about 22.0 m 2 / g.
[0055] The hydrotalcite prepared in Example 2 has a similar thermal stability effect to the hydrotalcite prepared by the sulfate hydrothermal method, but the production process of this process does not produce three wastes and has low energy consumption.
[0056] Example 3
[0057] This embodiment 3 provides a process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology, the process comprising the following steps:
[0058] S1, magnesium aluminum emulsion preparation: add 4700g of water into the preparation kettle, start stirring, then add 631g of magnesium hydroxide, 340g of aluminum hydroxide and 1.5g of grinding aid (Triton X100) into the preparation kettle, stir and mix, to obtain magnesium aluminum emulsion, grind it fully for at least 3 hours by grinding equipment at room temperature, and form magnesium aluminum emulsion that does not appear stratification for at least 48 hours after grinding, and set aside;
[0059] S2, crystallization reaction: take the above-mentioned low-temperature ground magnesium aluminum emulsion 3864g and add it to the reactor and add 3300g of water for dilution. After dilution, cover the reactor cover to ensure airtightness, turn on the high-temperature grinding equipment (the grinding equipment is made of zirconium oxide, of which zirconium oxide beads with a particle size of 50-100mm account for 5.0%, zirconium beads with a particle size of 10-50mm account for 10.0%, zirconium beads with a particle size of 5-10mm account for 15.0%, and zirconium beads with a particle size of 1-5mm account for 70%), turn on the ultrasonic dispersion device (100% opening), turn on the microwave heating device (70% opening) and heat it to the first temperature (110°C), and then perform high-temperature grinding and ultrasonic dispersion under closed conditions, and at the same time, after the feed liquid in the reactor is heated to the first temperature, start to slowly introduce a theoretical amount of carbon dioxide gas (CO 2 ) to introduce CO into the reaction system 3 2-Then, the temperature was slowly raised to the second temperature (190° C.) by microwave heating, and 65.0 g of carbon dioxide was introduced through a carbon dioxide metering device. After the introduction was completed, stirring and heat preservation were continued for 3 hours to carry out a crystallization reaction;
[0060] S3, modification: after the above-mentioned constant temperature reaction is completed, the reaction system is cooled to the third temperature (65°C), and then 2.0g of zinc stearate is added to the system and kept warm for 1 hour, and then 1.5g of stearic acid is added and the temperature is raised to 80°C and kept warm for 2 hours; then the temperature is cooled to the fourth temperature (below 80°C), and the material is pumped into a plate and frame filter press by a screw pump for filtration, thereby obtaining hydrated magnesium aluminum hydrotalcite;
[0061] S4. Drying: The above-mentioned hydrous magnesium aluminum hydrotalcite is dried by vacuum drying to obtain magnesium aluminum hydrotalcite, wherein the main component content is greater than 97%, the water content in the hydrotalcite is less than 0.5%, the particle size D90 is less than 1.8 μm, and the specific surface area is about 20.0 m 2 / g.
[0062] The hydrotalcite prepared in Example 3 has a similar thermal stability effect to the hydrotalcite prepared by the sulfate hydrothermal method, but the production process of this process does not generate three wastes and has low energy consumption.
[0063] Comparative Example 1
[0064] Hydrotalcite having the same magnesium-aluminum molar ratio as that in Example 1 was synthesized by a sulfate hydrothermal method.
[0065] Comparative Example 2
[0066] The difference between Comparative Example 2 and Example 1 is that the process of Comparative Example 2 does not perform low-temperature grinding and high-temperature grinding processes, and the rest is the same as Example 1.
[0067] test:
[0068] (1) Thermal stability test: The magnesium aluminum hydrotalcite prepared in Example 1, the magnesium aluminum hydrotalcite prepared in Comparative Example 1, the magnesium aluminum hydrotalcite synthesized by the method of Chinese patent CN107902681A, the magnesium aluminum hydrotalcite prepared in Comparative Example 2, and the commercially available Japanese Kyowa magnesium aluminum hydrotalcite were mixed uniformly at 190° C. using a high-speed mixer, and then pressed into a 1.0 mm thick sheet sample using a double-roll open mill;
[0069] ① Dynamic test: Cut the sample into 15cm*15cm pieces, and then put them into a rotary oven at 190℃. Take out a small amount of samples every 5 minutes and cut out 10mm*15mm sample, observe its color change; Among them, the changes of the samples prepared from the magnesium aluminum hydrotalcite obtained in Example 1 are as follows: Figures 4 to 13 As shown; the changes of the samples prepared by the magnesium aluminum hydrotalcite obtained by the method of patent CN107902681A are as follows Figures 14 to 23 As shown; the changes of the sample prepared by the magnesium aluminum hydrotalcite obtained in Comparative Example 1 are as follows Figures 24 to 33 As shown; the changes of the sample prepared by the magnesium aluminum hydrotalcite obtained in Comparative Example 2 are as follows Figures 34 to 43 As shown; the changes of the samples prepared by Concord Mg-Al hydrotalcite are as follows Figures 44 to 53 As shown; it can be seen from the above color change that the color of the sample prepared by the hydrotalcite of Example 1 of the present invention changes relatively slowly over time, which indicates that the hydrotalcite prepared by the present invention has better thermal stability;
[0070] ②Static test: Cut the remaining material into thin strips, put them into the mold in order, press them into static sheets with a thickness of 3.5mm*30mm*70mm, and observe the transparency of the static sheets;
[0071] The color change of the sample is observed in the dynamic test (the color changes from light to dark). The faster the color change, the worse the thermal stability of the sample, which can reflect the poorer thermal stability of the corresponding hydrotalcite; the poorer the transparency of the static sheet, the poorer the purity of the sample, reflecting the higher the content of unreacted magnesium oxide and aluminum oxide in the sample, and the transparency of the static sheet obtained in Example 1 is the highest; the above test can reflect the thermal stability of the corresponding hydrotalcite. From the results of the dynamic test and the static test, the analysis shows that the hydrotalcite synthesized by the process of the present invention has an excellent main component content of the sulfate hydrothermal method, good thermal stability, and high transparency of the test sample, indicating that the unreacted magnesium oxide and aluminum oxide impurities in the product are small and the product purity is high.
[0076] (2) Adsorption performance test: The magnesium aluminum hydrotalcite prepared in Example 1, the magnesium aluminum hydrotalcite prepared in Comparative Example 1 and the commercially available Japanese Kyowa magnesium aluminum hydrotalcite were mixed uniformly using a high-speed mixer according to the following formulas: 100.0 g of polyvinyl chloride (PVC), 30.0 g of dioctyl terephthalate (DOTP), 10.0 g of 52# chlorinated paraffin, 2.0 g of calcium zinc auxiliary stabilizer, 1.0 g of hydrotalcite, 8.0 g of processing aid and calcium powder. The mixture was extruded into strips through a single-screw extrusion platform and then cut into pellets with a length of 0.8 cm. 2.0 g of the pellets were weighed and placed in a test tube. The test tube was then placed in a Congo red tester at 200°C to record the Congo red. The test paper color change time and the final color of the sample show that the sample pellets containing the hydrotalcite in Example 1 adsorbed Congo red for 31 minutes, while the sample pellets containing the magnesium-aluminum hydrotalcite prepared in Comparative Example 1 and the sample containing the commercially available Japan Kyowa magnesium-aluminum hydrotalcite had an adsorption time of less than 30 minutes. The endpoint sample color of the sample pellets prepared with the hydrotalcite in Example 1 was dark red, while the endpoint sample color of the sample pellets prepared with the magnesium-aluminum hydrotalcite in Comparative Example 1 and the sample pellets prepared with the commercially available Japan Kyowa magnesium-aluminum hydrotalcite was dark brown, which indicates that the adsorption capacity of the hydrotalcite prepared in Example 1 is significantly higher than that of the magnesium-aluminum hydrotalcite prepared in Comparative Example 1 and the magnesium-aluminum hydrotalcite of Japan Kyowa.
[0077] The present invention provides a process for green synthesis of hydrotalcite using industrial-grade magnesium hydroxide, aluminum hydroxide, carbon dioxide as raw materials and a trace amount of external grinding aids, and the process adopts forced molecular recombination and diffusion technologies such as external additives, ultrasound, microwaves, low-temperature primary grinding, high-temperature and high-pressure grinding, etc. The whole process of the present invention is simple and easy to operate, the production process does not have three wastes, the method of fixing carbon dioxide is adopted, and the by-product water is recycled for many times. The system process solves the problem that the thermal stability effect in conventional production is unstable and the thermal stability effect of the later product is not as good as the stability effect of the product obtained by the sulfate water thermal method. The process of the present invention can maintain the characteristics of uniform particle size distribution and non-hardening of the produced hydrotalcite crystals, is convenient to use, and can be widely used in PVC heat stabilizers, cable and wire stabilizers, and high-transparency agricultural film anti-ultraviolet absorbers.
[0078] The above are preferred embodiments of the present invention and are only used to explain the present invention, not to limit the present invention. Any obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology, characterized in that: The process includes the following steps: S1. Preparation of magnesium-aluminum emulsion: In the presence of water, a magnesium source, an aluminum source and a grinding aid are stirred and mixed to obtain a magnesium-aluminum emulsion, and the emulsion is cryogenically ground for standby use; S2, crystallization reaction: dilute the low-temperature ground magnesium aluminum emulsion with water and heat it to the first temperature, then grind it at high temperature and disperse it ultrasonically under closed conditions, and introduce CO3 into the system after heating it to the first temperature. 2- and continue to raise the temperature to a second temperature to perform a crystallization reaction to promote the growth of magnesium-aluminum hydrotalcite grains; S3, modification: cooling the crystallization reaction system to a third temperature, then adding a modifier to the system for modification, and continuing to cool to a fourth temperature and filtering or centrifuging to obtain hydrous magnesium aluminum hydrotalcite; Wherein, the third temperature is lower than the first temperature; S4. Drying: Drying the hydrated magnesium aluminum hydrotalcite to obtain magnesium aluminum hydrotalcite.
2. The process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology according to claim 1, characterized in that: The magnesium source in step S1 is magnesium hydroxide, and the aluminum source is aluminum hydroxide; the grinding aid is used to prevent the magnesium-aluminum emulsion from agglomerating, and a polyether type grinding aid is selected.
3. A process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology according to claim 1 or 2, characterized in that: The magnesium aluminum emulsion comprises the following components: 5.0-16.0 wt% of magnesium source, 5.0-16.0 wt% of aluminum source, 0.01-0.03 wt% of grinding aid and the balance of water.
4. The process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology according to claim 1, characterized in that: The magnesium aluminum emulsion does not separate for at least 48 hours after cryogenic grinding.
5. The process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology according to claim 1, characterized in that: In step S2, the temperature is raised by microwave heating, and the first temperature is not lower than 100°C, and the second temperature is not higher than 200°C.
6. A process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology according to claim 1 or 5, characterized in that: Step S2: Introduce CO3 by slowly introducing carbon dioxide gas 2- After the addition is completed, continue to keep the reaction warm for 1 to 6 hours.
7. A process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology according to claim 1 or 5, characterized in that: The third temperature in step S3 is 55 to 85° C.; the modification time is 1 to 3 hours.
8. A process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology according to claim 1 or 7, characterized in that: The modifier in step S3 is stearic acid or stearate.
9. The process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology according to claim 1, characterized in that: The drying method in step S4 is boiling fluidized bed drying, blast drying, rake drying or vacuum drying.
10. The process for green synthesis of hydrotalcite by forced molecular recombination diffusion technology according to claim 1, characterized in that: The grinding equipment is made of zirconium oxide, of which zirconium oxide beads with a particle size of 50-100 mm account for 1-8%, zirconium oxide beads with a particle size of 10-50 mm account for 8-12%, zirconium oxide beads with a particle size of 5-10 mm account for 5-15%, and zirconium oxide beads with a particle size of 1-5 mm account for 50-70%.
